Zinc in different periods of pregnancy: A study on pregnant women of high and low socio-economic levels. - Trindade, Cleide Enoir Petean [UNESP]; de Souza Queiroz Tonete, Suzana [UNESP]; Sartori, Maria Eneida Aiello [UNESP]; de Nobrega, Fernando José; Rudge, Marilza Vieira Cunha [UNESP]; Tonete, José Teodore Veneziano; Filho, Sebastiao Camargo Schimidt (Taylor & Francis, 1984)
We have measured zinc in the serum of pregnant and non-pregnant women classified in two socio economic levels, high socio-economic level pregnant and non-pregnant women attending a private office and low socio-economic level pregnant and nonpregnant women either attending our hospital, belonging to a social welfare or not. The samples in the pregnant women were collected in the first, second and third trimesters of pregnancy. The socio-economic condition was proved to be important when comparing both groups of pregnant women. Such differences had already been remarked in the non-pregnant women group where the serum concentration was statistically greater at a higher socio-economic condition. Also both groups had different behaviours during the pregnancy. The women having a high socio-economic condition did not present any remarkable difference during the pregnancy whereas the low socio-economic condition ones, showed in the third trimester, zinc levels significantly lower than in the second trimester of pregnancy. © Gordon and Breach Science Publishers, Inc., 1984